Analysis of the Relationship Between Digital Literacy and Entrepreneurship Education on Entrepreneurial Readiness: the Role of Self-Efficacy in Vocational High School Students in Lumajang Regency in the Digital Era - Sumiati, Sumiati; Pratikto, Heri; Dhewi, Titis Shinta (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the influence of digital literacy and entrepreneurship education on the entrepreneurial readiness of SMKS students in Lumajang Regency, with self-efficacy as a mediating variable. The theories used in this study are the Theory of Planned Behavior and Social Cognitive Theory. The research method is quantitative descriptive with an explanatory approach, involving 208 respondents from five SMKS. Data were collected through online questionnaires and analyzed using Smart PLS. The results showed that digital literacy and entrepreneurship education positively affect self-efficacy, which in turn increases students' entrepreneurial readiness. These findings emphasize the importance of developing digital literacy and entrepreneurship education in building positive attitudes and entrepreneurial readiness among students and providing recommendations for further research with additional variables and broader subjects.